The Market Economy and the State - Paliulytė, Regina (Ekonomika, 1997)
The problem of the relationship between the state and the market and the functions of the state in the economy are analyzed in the article. Cases from Germany are used to illustrate theoretical statements. Every country, creating a model of its own economy, chooses’ adequate principles of economic order. One or another concept of economic development is accepted according to the particularity of the country. state of the economy. level of development of the state, way of training. experience of the previous periods of development. and requirements of the modem approach. These features form a specific relationship between the market and the state. This relationship alters under the circumstances. The change of relationship between the state and the market forces in favor of the market is reflected in the New Program of the German Government.